An observational study of emotion regulation in children with Tourette syndrome. (24th December 2020) - Hagstrøm, Julie; Spang, Katrine S.; Vangkilde, Signe; Maigaard, Katrine; Skov, Liselotte; Pagsberg, Anne Katrine; Jepsen, Jens Richardt Møllegaard; Plessen, Kerstin Jessica
Abstract : Background: Explosive outbursts occur in 25%–70% of children with Tourette syndrome (TS) and may cause more distress than the tics themselves. Previous studies have indicated that a comorbid diagnosis of attention‐deficit/hyperactivity disorder (ADHD) is associated with emotional dysregulation in TS; however, this relationship has almost exclusively been studied using parent‐reported questionnaires. Methods: We examined emotion regulation (ER) with an observational measure in 150 medication‐naïve children aged 7–12 allocated to four groups: Forty‐nine children with TS, 23 children with ADHD, 16 children with TS + ADHD, and 62 typically developing controls. We assessed participants' ER ability, as well as parent–child interactions in the context of a complex puzzle task, and coded the observed behavior with the Tangram Emotion Coding Manual (TEC‐M). We examined group differences in ER, as well as associations between ER and severity of symptoms pertaining to TS and ADHD. Results: Children with TS did not differ from controls in their ER ability. However, children with ADHD and TS + ADHD had more problems with ER than those with TS only and controls. Finally, parents of children with ADHD displayed more tension during the experimental task. ER ability was not associated with tic severity nor premonitory urges; however, better ER ability was associated with less severe symptoms of ADHD. Conclusions: This study is the first to evaluate ER with an observational, clinician‐rated measure in a controlled social setting in children with TS. Our findings support earlier questionnaire‐based studies by showing impaired ER in children with TS + ADHD, but not in children with TS without comorbidity. These findings inform our understanding of the phenomenology of emotional dysregulation in TS and the role of comorbid disorders.